EMPREENDER NA CRISE: as dificuldades de uma microempresa na pandemia de COVID-19 - Ezio Joao Stranieri Junior (2021)
Micro and Small Enterprises (MPEs) are very important to the Brazilian economy, as these companies are responsible for more than half of formal jobs in the country, contributing 30% of the Gross Domestic Product (GDP), and even with all this importance, almost 1 /4 of them disappear in the first two years of existence (Sebrae, 2016). The reasons for the disappearance are diverse. But, if that wasn't enough, and to make the situation even worse, in 2020, we have the spread of the new coronavirus (COVID-19), which affects the economy of the country and the world. One of the reasons, in addition to illness and loss of life, were the measures taken by the authorities to try to slow down the contagion, such as social isolation, quarantine and even the closing of borders, which made the pandemic have become one of the worst financial crises the world has witnessed since the 1929 crisis. From this context, this study aims to identify the main difficulties that a microenterprise manager faces in continuing his business and how management accounting can help in those moments. The research used a qualitative approach with an exploratory methodology, adopting documentary research and narrative in the construction of evidence, Grounded Theory as a data analysis strategy, with the support of the Iramuteq program. According to the data analyzed in the research and the literature consulted, small entrepreneurs are facing several difficulties generated by the current crisis caused by COVID-19, and the main difficulty is in taking out loans for working capital. Another important aspect was the lack of qualification of the manager to manage his company, making access to the information system and the use of managerial information difficult. As these companies usually do not have the financial conditions to hire a specialized consultancy, the support of the Accountant at these times is essential to help the manager understand this information. Thus, this research intends to contribute to the understanding of management accounting aspects and to the reduction in the mortality rate in a crisis context.